DEVELOPMENT OF E-MODULE PROJECT BASED LEARNING MODEL IN SERVER ADMINISTRATION BASICS CLASS XI COMPUTER ENGINEERING AND NETWORKS IN SMK NEGERI 3 SINGARAJA. - Adi Kusuma, I Wayan Wilantara; Santyadiputra, Gede Saindra; Sindu, I Gede Partha (Jurusan Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2018)
ABSTRACTThe purpose of this study (1) In order to implement the results of the E-Module Project Based Learning Model in Server Administration Basics Class XI Computer Engineering and Networks in SMK Negeri 3 Singaraja. (2) To study the response of teachers and students towards the development of E-Module Project Based Learning Model in Server Administration Basics Class XI Computer Engineering and Networks in SMK Negeri 3 Singaraja developed.The type of the research used in this study was Research and Development using ADDIE development model. The subjects of the study were the eleven grade students of Computer Engineering and Networks at SMK Negeri 3 Singaraja in academic year 2017/2018. In order to identify the teachersâ and studentsâ respond toward the e module of Network Design, questionnaire was used to obtain the data. The results obtained shown that (1) the results of the E-ModuleÂ Project Based Learning Model in Server Administration Basics Class XI Computer Engineering and Networks in SMK Negeri 3 Singaraja otherwise successfully applied by some of the tests conducted. (2) The results of the analysis show that the teacher response data, obtained an average score of response was 43 when converted into the classification table, the response included in the category of positive. As for the students response to the development of e-modules obtained an average score of 60.78 response, if converted into a table classifying student responses included in the category of positive. Â Â Keywords: E-Module, ADDIE, Server Administration, Project Based Learning